Analysis of the epidemiological profile and quality of life of patients after transcatheter aortic valve implant procedure (TAVI) in a city of western Paraná (Research, Society and Development, 2023)
Introduction: Aortic stenosis is a coronary disease characterized by the narrowing of the aortic valve. If left untreated, it progresses over time and becomes symptomatic, potentially leading to heart failure and ultimately death. The standard treatment is open-heart surgery. However, a less invasive alternative technique has recently emerged. This innovation is known as transcatheter aortic valve implantation (TAVI). Objective: The present study aimed to describe the epidemiological profile of patients who underwent TAVI procedures in the hospital networks of Cascavel, Paraná. Materials and Methods: This was an observational study of a descriptive, cross-sectional, and retrospective nature, which collected subjective information about the quality of life of the interviewed patients before and after the procedure. Results: 26 patients were included in the sample. Thus, 22.7% reported experiencing some form of impairment in their daily activities before the procedure. After the procedure, 36.4% reported feeling very satisfied, and 59.1% reported being satisfied. Regarding symptoms, 50% reported a significant improvement, and 36.4% reported a significant improvement. Conclusions: Therefore, the majority of interviewed patients had a favorable outcome, reporting an improvement in their quality of life. However, further studies are needed to prospectively analyze the progression of these patients for a better understanding of potential complications and other associated factors.